Getting Recovery Right After Neck Dissection (GRRAND-F): mixed-methods feasibility study to design a pragmatic randomised controlled trial protocol. Issue 6 (21st June 2021) - Gallyer, Victoria; Smith, Toby O; Fordham, Beth; Dutton, Susan; Chester-Jones, Mae; Lamb, Sarah E; Winter, Stuart C
Abstract : Introduction: We will evaluate the feasibility of a randomised controlled trial to estimate the effectiveness and cost-effectiveness of a rehabilitation intervention on pain, function and health-related quality of life following neck dissection (ND) after head and neck cancer (HNC). Methods and analysis: This is a pragmatic, multicentred, feasibility study. Participants are randomised to usual care (control) or usual care plus an individualised, rehabilitation programme (Getting Recovery Right After Neck Dissection, GRRAND intervention). Adults aged over 18 with HNC for whom ND is part of their care will be recruited from specialist clinics. Participants are randomised in 1:1 ratio using a web-based service. The target sample size is 60 participants. Usual care will be received by all participants during their postoperative inpatient stay consisting standard National Health Service care supplemented with a booklet advising on postoperative self-management strategies. The GRRAND intervention programme consists of usual care plus up to six individual physiotherapy sessions including neck and shoulder range of motion (ROM) and progressive resistance exercises, advice and education. Between sessions participants will be advised to complete a home exercise programme. The primary outcome is to determine recruitment and retention rates from study participants across sites. Outcomes will be measured at 6 and 12 months. Participants and physiotherapists will be invited to an optional qualitative interview at the completion of their involvement in the study. The target qualitative sample size is 15 participants and 12 physiotherapists. Interviews aim to further investigate the feasibility and acceptability of the intervention and to determine wider experiences of the study design and intervention from patient and physiotherapist perspectives. Ethics and dissemination: Ethical approval was given on 29 October 2019 (National Research Ethics Committee Number: 19/SC/0457). Results will be reported at conferences and in peer-reviewed publications. Trial registration number: ISRCTN11979997 . Status: Trial recruitment is ongoing and is expected to be completed by 30 August 2021.